Моделювання процесів надійності в системах, що не відновлюються - Корсунська, Я. Є. (ХНУРЕ, 2020)
The solution to the problem of ensuring the reliability of the equipment is primarily related to the development of theoretical methods of reliability analysis at the design stage, which lays the foundation for the reliability of the developed equipment. One of the modern ways of solving this problem is to use methods based on probabilistic modeling. The simplest implementation of this method is in the case of modeling of reliability processes in non-renewable systems.
Keywords: надійність апаратури; імовірність безвідмовної роботи